Perspektiewe uit die Psalms wat lig werp op die wese van die geloofsgemeenskap - Bezuidenhout, L. C. (Hervormde teologiese studies, 1995)
Perspectives from the Psalms which illuminate the essence of the community of faith. The Psalms functioned in contexts which were quite different from that'of the modem church, yet they can contribute to a better understanding of the essence of the community of faith. The spirit of a community is revealed in its art more than in its laws. The Psalms constitute the aesthetic residue of the ancient community of faith. Although they do not entail definite laws or regulations concerning the community of faith, they bear witness to the spirituality of the ancient community of faith. In the Psalms certain values can be discerned which are applicable to the modem church.